Destination recovery during COVID-19 in an emerging economy: Insights from Perú - Jesús J. Cambra-Fierro; María Fuentes-Blasco; Rocío Huerta-Álvarez; Ana Olavarría-Jaraba (European Research on Management and Business Economics (ERMBE), 2022)
The onslaught of the COVID-19 pandemic has had a critical impact on the travel and tourism sector. Tourist destinations in developing countries are even more susceptible to negative trends of this sort due to the importance of tourism in emerging economies and the peculiarities of their infrastructures and healthcare systems. In such a context, the research develops a Partial Least Square (PLS) path modeling to analyze the impact of destination image and perceived health safety on perceived destination quality. We also assess the extent to which perceived quality impacts degree of destination loyalty and customer engagement. Results are based on a sample of 250 travelers visiting Lima during December 2020-January 2021.
Keywords: M31; 650; Customer engagement; Destination image; Destination loyalty; Perceived health safety; Perceived quality